1983
DOI: 10.1017/s0022112083003201
|View full text |Cite
|
Sign up to set email alerts
|

Noise generated by airfoil profiles placed in a uniform laminar flow

Abstract: The present paper is devoted to the experimental study of the noise generated by an airfoil profile placed in a uniform laminar flow. The far-field acoustic spectrum is shown to be composed of a broadband contribution around frequency f, and a discrete contribution a t equidistant frequencies f,, which follow power laws of the forms f ,-P 5 and f,-U0.85. Both contributions can be accounted for by a simple model derived from the original suggestions of Tam (1974) and Fink (1975). It is essentially assumed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
221
5
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(262 citation statements)
references
References 13 publications
35
221
5
1
Order By: Relevance
“…In this velocity range the spectrum is characterized by numerous and equally-spaced discrete frequencies (sometimes as many as 10 at a single velocity). Identical behaviour is found in the experimental and numerical works of [2,3,5,7,23]. For the S1, S2 and S3 serrations, there is no sudden jump in OASPL at 20 ms -1 < v j < 60 ms -1 and it is found that OASPL (S1, S2, and S3)  v j…”
Section: 4supporting
confidence: 69%
See 3 more Smart Citations
“…In this velocity range the spectrum is characterized by numerous and equally-spaced discrete frequencies (sometimes as many as 10 at a single velocity). Identical behaviour is found in the experimental and numerical works of [2,3,5,7,23]. For the S1, S2 and S3 serrations, there is no sudden jump in OASPL at 20 ms -1 < v j < 60 ms -1 and it is found that OASPL (S1, S2, and S3)  v j…”
Section: 4supporting
confidence: 69%
“…1). Based solely on Model A, the tonal frequencies can be predicted [2,3,5] from the frequencies, f n , at which the phase change around the loop 2F(f n ), given by…”
Section: Assessment Of Feedback Mechanism Based On Model Amentioning
confidence: 99%
See 2 more Smart Citations
“…This was followed by an identification of multiple frequency peaks (see, e.g. Arbey & Bataille, 1983) and a resulting ladder structure as the free-stream velocity is varied. The multi-peak structure has been confirmed in further experiments as well as in numerical simulations by, e.g., Desquesnes et al (2007); Jones & Sandberg (2011);Fosas de Pando et al (2014) and has been linked to feedback loops consisting of boundary layer instabilities and acoustic radiation.…”
Section: Introductionmentioning
confidence: 99%